A class of ratio distributions of dependent folded normals and its applications. Issue 4 (3rd July 2016) - Kim, Hea-Jung
Abstract : If U has a normal distribution, then | U | is said to have a folded normal distribution . The distribution can be viewed as one involving normal measurements without their algebraic sign. As a natural extension of the distribution, we propose a distribution of the ratio of two correlated folded normals and demonstrate its statistical applicability by considering some properties of the distribution. Necessary theories on the expectation of a function of | U | are provided to derive the properties. Likelihood inference for the proposed distribution is developed, and a simulation study is implemented to verify the inference. Further, four examples are presented to illustrate the practical application of the distribution.